Nature Tourism in Muar River Valley - Khoo, Pei Ying; Mohamed, Maryati; Dalimin @ Dolimin, Mohd Noh (Journal of Sustainable Natural Resources, 2022)
Sungai Muar or Muar River is special. Passing through three states of Peninsular Malaysia, it originates in Negeri Sembilan, passes briefly in Malacca, into Johor and ends into the Straits of Malacca. Though laden with history and presently undergoing much socio-economic development, the importance of this river remains inconspicuous, as it is simply known as Sungai Muar. This paper proposes that a geographical official entity be recognized for this river and its surrounding areas as Muar River Valley (MRV) or in Malay, Lembangan Sungai Muar to enhance any future planning and development which would be site-based, thus giving due recognition to the river. Essential data was researched to produce two maps. The first map is for geophysical information of MRV, which forms the first objective of the research. To realistically prove its importance as an official entity, the tourism development was chosen. This research examined previous and potentially new nature tourism research. These are then marked on the map and thus a simple visual appreciation to understand the potential of nature tourism of MRV is easily seen. Hence, the second map is for existing tourism activities and potential tourism destinations and products in MRV. This forms the second objective. To further enhance, that venture such as nature tourism, could increase the appreciation to the importance of MRV, a nature tourism product development was done and described, forming the third objective. The exemplary product development is based on a newly recognized oyster species, endemic to MRV named as Crassostrea (Magallana) saidii. All data for the three objectives were obtained through literature search using search engine like Google. Additional methods include interviewing through phone calls, face-to-face, and also Google Meet. The information related to land use, and drainage and irrigation system around Bandar Maharani are obtained, along with the topography around the extent of Muar District are obtained as well, as basic requirement for the proposal of MRV. Finally the newly recognized oyster is developed into a tourism product of which the 3 hours package include activities such as observing traditional harvesting of the oysters and tasting of oyster dishes. To complete the nature tourism product development, prototypes of souvenirs are made from shells of the new oysters. For conservation purpose, souvenirs were also made from common species. This recommendation to officiate the designation of MRV would be made to the state government of Johore, through the Muar District Office.